PENGARUH LITERASI DIGITAL DAN KONFORMITAS TERHADAP MINAT TECHNOPRENEURSHIP MAHASISWA: (Survei pada Mahasiswa Jurusan Pendidikan Ekonomi Universitas Siliwangi Angkatan 2019) - Perdana, Rahmadi Nanda Putra; Sadiah, Ati; Kurniawan (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
This study addresses students' limited interest in technopreneurship and examines the impact of Digital Literacy and Conformity on Technopreneurship Interest. Using a quantitative survey approach with an explanatory design, the research involves 104 Economics Education students from Universitas Siliwangi (2019 cohort). Employing saturated sampling, data collection utilizes questionnaires and analysis includes multiple linear regression with t-test and F-test. Findings reveal high levels of Technopreneurship Interest (7.996), Digital Literacy (7.681), and Conformity (5.543). Digital Literacy significantly positively influences Technopreneurship Interest (p < 0.05), as does Conformity (p < 0.05). Simultaneously, Digital Literacy and Conformity collectively impact students' Technopreneurship Interest significantly (p < 0.05, coefficient of determination 60.9%). These outcomes emphasize the influential role of Digital Literacy and Conformity in shaping students' interest in technopreneurship.